An analysis of the hydrogen explosion in the Fukushima-Daiichi accident. (6th July 2015) - Yanez, J.; Kuznetsov, M.; Souto-Iglesias, A.
Abstract An analysis of the amount of hydrogen taking part in the explosions that happened during the Fukushima-Daiichi (Unit 1) nuclear power plant accident is presented herein. Through a series of analytic approximations and numerical calculations of increasing complexity, it has been possible to estimate that 130 kg of H2 was involved in the explosion. Also, the strength of the resulting explosion was examined determining that even with a significantly smaller amount of hydrogen taking part, a devastating explosion would have occurred regardless.